Effect of Time and Temperature on Moisture Content, Shrinkage, and Rehydration of Dried Onion (Iranian Journal of Chemical Engineering)
In this paper, the experimental data of the onion drying process by a batch cabinet dryer is investigated. Obtained experimental data including moisture content, shrinkage, and rehydration via random factorial scheme are analyzed. Comparison of data average is carried out with the help of the multi amplitude test of Duncan. Statistical analysis of experimental data shows that time, temperature, and their combined effect have a reasonable impact on the moisture content and rehydration value of dried samples. However, a combined effect of time and temperature on the shrinkage value is not meaningful (P>0.05). The results also show that increasing time and temperature leads to a decrease in the moisture content of the samples, but it increases the value of rehydration and the shrinkage of samples.